The Over-expression of the Plastidial Transglutaminase from Maize in Arabidopsis Increases the Activation Threshold of Photoprotection - Ioannidis, Nikolaos E.; Malliarakis, Dimitris; Torné, Josep M.; Santos, Mireya; Kotzabasis, Kiriakos (Frontiers in Plant Science, 2016)
Plastidial transglutaminase is one of the most promising enzymes in chloroplast bioenergetics due to its link with polyamine pathways and the cross talk with signals such as Ca+2 and GTP. Here we show the effect of the increase of transglutaminase activity in Arabidopsis by using genetic transformation techniques. These lines fulfill their biological cycle normally (normal growth in soil, production of viable seeds) and show a relatively mild increase in transglutaminase activity (127%). These overexpressors of transglutaminase (OE TGase) have an extended stroma thylakoid network (71% higher number of PSIIβ centers), similar chlorophyll content (-4%), higher linear electron flow (+13%) and higher threshold of photoprotection activation (~100%). On the other hand OE TGase showed a reduced maximum photochemistry of PSII (-6.5%), a smaller antenna per photosystem II (-25%), a lower photoprotective “energization” quenching or qE (-77% at 490 μmolphotonsm-2s-1) due to a higher threshold of qE activation and slightly lower light induced proton motive force (-17%). The role of the polyamines and of the transglutaminase in the regulation of chemiosmosis and photoprotection in chloroplasts is discussed.